Cartel Sustainability and Cartel Stability - Marc Escrihuela-Villar (Fondazione Eni Enrico Mattei (FEEM), 2004)
The paper studies how does the size of a cartel affect the possibility that its members can sustain a collusive agreement. I obtain that collusion is easier to sustain the larger the cartel is. Then, I explore the implications of this result on the incentives of firms to participate in a cartel. Firms will be more willing to participate because otherwise, they risk that collusion completely collapses, as remaining cartel members are unable to sustain collusion.
Keywords: L11; L13; L41; D43; 330; Collusion; Partial cartels; Trigger strategies; Optimal punishment; Kartell; Theorie